Negative regulation of urokinase receptor activity by a GPI-specific phospholipase C in breast cancer cells - van Veen, Michiel; Matas-Rico, Elisa; van de Wetering, Koen; Leyton-Puig, Daniela; Kedziora, Katarzyna M; De Lorenzi, Valentina; Stijf-Bultsma, Yvette; van den Broek, Bram; Jalink, Kees; Sidenius, Nicolai; Perrakis, Anastassis; Moolenaar, Wouter H (Elife, 2017)
The urokinase receptor (uPAR) is a glycosylphosphatidylinositol (GPI)-anchored protein that promotes tissue remodeling, tumor cell adhesion, migration and invasion. uPAR mediates degradation of the extracellular matrix through protease recruitment and enhances cell adhesion, migration and signaling through vitronectin binding and interactions with integrins. Full-length uPAR is released from the cell surface, but the mechanism and significance of uPAR shedding remain obscure. Here we identify transmembrane glycerophosphodiesterase GDE3 as a GPI-specific phospholipase C that cleaves and releases uPAR with consequent loss of function, whereas its homologue GDE2 fails to attack uPAR. GDE3 overexpression depletes uPAR from distinct basolateral membrane domains in breast cancer cells, resulting in a less transformed phenotype, it slows tumor growth in a xenograft model and correlates with prolonged survival in patients. Our results establish GDE3 as a negative regulator of the uPAR signaling network and, furthermore, highlight GPI-anchor hydrolysis as a cell-intrinsic mechanism to alter cell behavior.
Keywords: Receptores celulares; Citología; GDE3; cancer biology; Gglycerophosphodiester phosphodiesterase; signal transduction.; cell biology; glycosylphosphatidylinositol; human